MATHEMATICS EDUCATORS’ PERSPECTIVES ON CULTURAL RELEVANCE OF BASIC LEVEL MATHEMATICS IN NEPAL - Bed Raj Acharya; Mukunda Prakash Kshetree; Bishnu Khanal; Ram Krishna Panthi; Shashidhar Belbase (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2021)
The main purpose of this paper was to explore mathematics educators’ perception of the cultural relevance of basic level mathematics in Nepal. The design of this study involved an interpretive qualitative approach by administering in-depth interviews with five purposively selected mathematics educators teaching at five higher education institutions in the Kathmandu valley. Each interview was audio-recorded and transcribed for coding and constructing themes. The major themes that emerged were teaching in a mother language, contextualized Ethnomathematics, and the local knowledge in the curriculum as a teaching approach. The findings of the study can be helpful to curriculum designers and teachers at the basic level of mathematics. The study also adds to the literature of cultural aspects of mathematics teaching and learning and curriculum design.